Multiple Casualty Scenario from a Bomb/Blast Injury - Benjamin Weston; Nicholas Simpson; Danielle Hart; Lisa Fitzgerald-Swenson; John Hick (Association of American Medical Colleges, 2015)
Abstract The purpose of this resource is to provide emergency medicine residents with an opportunity to practice triaging and caring for patients in a mass casualty situation. This scenario includes seven high-fidelity simulators and five standardized patients as casualties. The learners have an opportunity to improve their skills in managing and prioritizing multiple casualties, including patients with less commonly seen injuries in civilian practice, such as amputations and junctional (femoral/axillary) wounds with significant hemorrhage. The implementation of this mass casualty scenario requires a large amount of time, manpower, and energy for execution. This involves coordinating approximately 20 persons involved in the scenario as confederates, staging managers, etc. This emphasizes the importance of all personnel arriving prepared and very familiar with the scenario and their roles. It also highlights the importance of having a functional and robust backchannel communication system, as in our experience, we required at least five active channels to work seamlessly without a problem. The importance of improvisation, as in any simulation, is also important in a scenario with seven simulators and five live patients, as the increased number of mannequins and actors increases the likelihood that things may not go exactly as planned. Despite all of these logistics that can be challenging to coordinate, we feel the return on investment of giving our trainees this experiential learning experience is worth the time and effort invested, as this is an experience that they will not get very frequently and may be relied on as the chief decision maker in future mass casualty situations.